A Recent Update: Solid Lipid Nanoparticles for Effective Drug Delivery - Sonia Pandey; Farhinbanu Shaikh; Arti Gupta; Purnima Tripathi; Jitendra Singh Yadav (Tabriz University of Medical Sciences, 2022)
Solid lipid nanoparticles are one of the developed technologies for addressing the bioavailability and targeting issues of drug delivery. In this review article, we attempted to incorporate all the essential details of SLNs like various methods of preparation, different models of SLNs, updated characterization methods, in-vivo behavior (Uptake), their applications, route of administration as well as advancements taken place in the field of delivery of biological drugs like gene vector, new adjuvant for vaccines, protein, and peptide with SLNs. Surface modified SLNs hold excellent potential for targeted and controlled drug delivery which is discussed and summarized. Based on the available data, the future success of SLNs is widened because they could be easily fabricated with various functionalities which would display enormous potential for targeting and diagnosing various diseases. This review would help the budding researchers to find out the unexplored areas of SLNs with the present discussion that reframes the potential of SLNs by gathering the various research findings of SLNs in tabular form along with the approved patent technologies of SLNs.